Multilevel mechanisms of in-and-out-of-class integrated physical education on adolescents’ physical health: a qualitative study based on socio-ecological and social cognitive theories - Yali, Han; Woong-jae, Choi (Frontiers in Education, 2025)
IntroductionThe adolescent physical health crisis has become a core challenge in the global fields of public health and education. Due to factors such as long-term sedentary behavior, lack of physical activity, and increased screen time, adolescents’ physical health presents the characteristics of “double highs and double lows”—the obesity rate and myopia rate keep rising, while physical fitness and sports ability generally decline. As an emerging intervention method to address this issue, the internal mechanism of the “In-and-Out-of-Class Integration (IOCI)” physical education teaching model under the cross-theoretical framework has not been systematically explained. Although the Social Ecological Model (SEM, covering five levels of environment: individual, interpersonal, organizational, community, and policy) and Social Cognitive Theory (SCT, focusing on the cognitive mechanisms of self-efficacy, observational learning, and behavioral ability) respectively reveal the independent influences of environmental levels and individual cognition, the synergistic logic of the two in the intervention of adolescent sports behavior still needs to be broken through, and the relevant theoretical gaps urgently need to be filled.MethodsWith the integrated dual-theoretical framework of SEM and SCT as the core, this study adopted a mixed qualitative research design to explore the mechanism of the IOCI model on adolescents’ physical health: 1) The research subjects were selected from 3 middle schools in Qingdao with remarkable IOCI practice effects, and 120 respondents (including students, physical education teachers, parents, and community workers) were identified through purposive sampling and snowball sampling; 2) Data collection was conducted using semi-structured interviews (30-60 minutes per person, with full recording and transcription into text), field observations (recording physical education classes, extracurricular sports activities, and community sports scenarios), and text analysis (sorting out school teaching plans, policy documents, and home-school communication records); 3) For data analysis, NVivo 12 software was used for grounded theory coding (127 initial nodes generated through open coding, 23 sub-categories classified through axial coding, and 5 core categories extracted through selective coding). Triangulation and theoretical saturation test (no new coding appeared in 5 consecutive interviews) were used to ensure data credibility, and an international comparative perspective was introduced to enhance the universality of the theory.ResultsIndividual Cognitive Engine: Adolescents gained “successful experiences” by mastering sports skills such as basketball three-step layup and rope skipping rhythm control, forming the core psychological driving force for behavioral change along the path of “successful experience → improved self-efficacy → active participation. Meanwhile, sports demonstrations by parents/peers (e.g., the “demonstration-imitation” chain of family cycling) further activated the observational learning mechanism; 2) Environmental Synergy Network: At the micro-meso level, the school’s “basic + specialized + characteristic” curriculum system and the family’s “emotional companionship - sports habit transmission” mechanism formed an “interest-driven - environmental response” closed loop; at the macro level, the community’s “venue sharing + professional guidance” model (including intelligent reservation systems and social instructor support) and the “sports-education integration assessment” policy (e.g., incorporating physical health into government performance evaluation) built a rigid resource guarantee; 3) Cross-level Emergent Effect: A snowball-like synergy mechanism of “family support → school feedback → community participation” was discovered, which effectively broke through the limitations of traditional single-level intervention and achieved the intervention effect of multi-level linkage.DiscussionThis study realized the in-depth integration of the SEM five-level environmental framework and the SCT cognitive mechanism for the first time, filling the theoretical gap of “environmental structure - cognitive mediation - behavioral change”—it not only improved SCT’s interpretation of environmental structural constraints (e.g., the participation rate issue in resource-poor communities) through SEM, but also supplemented SEM’s interpretation of individual psychological processing (e.g., differences in individual participation enthusiasm in the same venue) with SCT. In terms of practice, the “individual-interpersonal-organizational-community-policy” synergy path revealed by the study provides specific basis for the optimization of the IOCI physical education teaching model, such as schools needing to strengthen the design of personalized courses and communities and families needing to deepen resource linkage. Methodologically, this study provides a reference paradigm for cross-theoretical qualitative research in the field of physical education.